Factors Predicting Single-Unit Predominance after Double Umbilical Cord Blood Transplantation - Ramirez, Pablo (2011)
Double umbilical cord blood transplantation (dUCBT), developed as a strategy to treat larger patients with hematologic malignancies, frequently leads to the long-term establishment of a new hematopoietic system maintained by cells derived from a single UCB unit. However, predicting which unit will predominate has remained elusive. This retrospective study examined risk factor associated with unit predominance in 262 patients with hematologic malignancies who underwent dUCBT with subsequent hematopoietic recovery and complete chimerism between 2001–2009. Dual chimerism was detected at day 21–28, with subsequent single chimerism in 97% of cases by day +100 and beyond. Risk factors included nucleated cell dose, CD34+ and CD3+ cell dose, colony forming units-granulocyte macrophage dose, donor-recipient human leukocyte antigen (HLA) match, sex and ABO match, order of infusion, and cell viability. In the myeloablative setting, CD3+ cell dose was the only factor associated with unit predominance (OR 4.4, 95%CI, 1.8–10.6; p<0.01), but in the non-myeloablative setting, CD3+ cell dose (OR 2.1, 95%CI, 1.0–4.2; p=0.05) and HLA match (OR 3.4, 95%CI, 1.0–11.4; p=0.05) were independent factor associated with unit predominance. Taken together, these findings suggest that immune reactivity plays a role in unit predominance and should be considered during graft selection and graft manipulation.